Long-term water absorption tests for frost insulation materials taking into account frost attack - Toni A. Pakkala; Jukka Lahdensivu (Case Studies in Construction Materials, 2014)
Water absorption of several different frost insulation materials was tested for four years. The test took into account both immersion and frost attack to materials. On the basis of the research the water absorption on XPS specimens is significantly minor compared to EPS specimens that were studied. The most significant result was that freezing of test specimens did not affect on water absorption of XPS specimens but had a major effect on water absorption of EPS specimens. With frozen EPS specimen the absorption continued increasing even after 48 months of immersion. Presumably the reason for such a behaviour is that the pore structure of EPS is not able to resist the tension caused by freezing water and therefore cracks are formed. Thus, more water absorbs inside the EPS through the cracks and it causes cracking deeper in the specimen which is why absorption increases after every freezing period.